Management Pattern of the Arabic Language Learning Program in a Yellow Book–Based Islamic Boarding School at Nadwa Sinunukan Islamic Boarding School - Siti Sumaiah Batubara; Erka Pulungan; 'Aidil 'Azza Mu'izzuddin; Hakmi Wahyudi (Universitas Islam Negeri Palopo, 2026)
Studies on Arabic language learning in Islamic boarding schools have predominantly focused on instructional methods, while limited attention has been given to how educational management supports the effectiveness of kitab kuning-based learning programs. This study aims to analyze the management model of the Arabic language learning program based on kitab kuning at Nadwa Sinunukan Islamic Boarding School and to examine its contribution to students’ mastery of classical Islamic texts. Employing a descriptive qualitative approach, data were collected through interviews, observations, and documentation involving the pesantren leader, Arabic language teachers, and students. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the pesantren implements an integrated management model that combines systematic planning, teacher coordination, structured learning schedules, and continuous evaluation with traditional pesantren learning methods, including bandongan, sorogan, and discussion. This management pattern enables the alignment of institutional goals, instructional practices, and student learning outcomes in mastering nahwu and sharaf as the foundation for understanding kitab kuning. The study highlights the uniqueness of integrating modern management functions with traditional pesantren pedagogical practices. The findings contribute to the discourse on Islamic educational management by demonstrating that effective program management can strengthen the sustainability and effectiveness of kitab kuning-based Arabic learning. Practically, the study offers a management framework that may serve as a reference for other pesantren seeking to improve students’ competence in reading and understanding classical Islamic texts.